Balance and cognitive impairments are prevalent and correlated with age in presurgical patients with essential tremor. (2022) - Campbell, Justin M.; Ballard, Jim; Duff, Kevin; Zorn, Meghan; Moretti, Paolo; Alexander, Matthew D.; Rolston, John D.
Highlights: Most presurgical patients with ET (87%) met criteria for reclassification as "ET-plus" Balance and cognitive impairment are very common in patients with essential tremor. Preoperative assessment of balance and cognitive impairment is warranted and may influence surgical outcome. Abstract: Introduction: Essential tremor (ET) was long considered a monosymptomatic disorder, but this view has given way to a more comprehensive clinical picture that involves consideration of non-tremor symptoms (e.g., balance impairment, cognitive impairment). Recently, the novel designation of "ET-plus" was proposed to reclassify ET patients who demonstrate these non-tremor clinical features, but the prevalence of ET-plus remains poorly defined. The primary aim of our study was to estimate the prevalence of ET-plus among presurgical patients with ET by applying this reclassification scheme. Methods: We performed a retrospective review of patients with ET being considered for deep brain stimulation or focused ultrasound thalamotomy. Patient demographics and data from their clinical workups were collected. As part of their clinical workup, patients were screened for preexisting balance and cognitive impairment. Patients with ET were designated as ET-plus if they had balance impairment, cognitive impairment, or tremor at rest. We performed a series of Pearson correlations to examine how individual clinical and demographic variables were related. Results: We identified 92 patients who met the study criteria. Our results indicate that 87% of the presurgical patients in our cohort met the criteria for reclassification as ET-plus. In addition, we observed robust correlations between patient age and balance impairment, cognitive impairment, history of falls, family history of tremor, and ET-plus reclassification. Conclusion: We propose that balance and gait impairment should be assessed preoperatively alongside neuropsychological evaluation to improve the counseling and treatment of patients with ET-plus.